Organotin Pollution in China - Qun-fang Zhou; Gui-bin Jiang; Ji-yan Liu (The Scientific World Journal)
A preliminary investigation of the occurrence of butyltin compounds was made in various environmental samples including water, sediment, sea products, and other commodities from China. Detection was carried out by the method of hydrogenation coupled with SPME or Grignard derivatization, followed by GC-FPD analysis. The results showed the universal existence of butyltin compounds in a wide range of tested samples, which was a potential danger for human health. Urgent control or management of organotin compounds is necessary to prevent the underlying hazard caused by this kind of pollutant.